Analisis Perspektif Pemasaran Syariah terhadap Praktik Gimmick Marketing pada UMKM Coffee Kawansenja_id - M. Ja’far Fikri; Kusnul Cipta Nila Yuni (Journal of Economics, Management, and Accounting, 2026)
This study aims to analyze the use of gimmick marketing by the Coffee Kawansenja_id SME from a sharia marketing perspective amid the transformation of digital business communication based on social media. The study employs a qualitative approach using a case study design through digital observation, in-depth interviews, and documentation of promotional content on Instagram and TikTok. The findings reveal that Coffee Kawansenja_id leverages aesthetic visual strategies, viral trends, emotional narratives, and customer testimonials to foster emotional engagement and strengthen brand positioning among young consumers. These strategies have proven effective in increasing digital interaction and shaping a brand identity based on symbolic experiences. Sharia marketing analysis reveals that promotional practices reflect the principles of shiddiq, amanah, tabligh, and fathanah in terms of polite, adaptive, and relatively transparent communication, although issues related to the use of non-original visuals and a tendency toward the commodification of emotions in digital content were still identified. The research confirms that the success of sharia SME marketing in the digital era is determined by the ability to integrate promotional creativity with moral integrity, authentic communication, and sustainable social responsibility.